Long Term Time-Lapse Imaging of Geographic Atrophy: A Pilot Study - Paques, Michel; Norberg, Nathaniel; Chaumette, Céline; Sennlaub, Florian; Rossi, Ethan; Borella, Ysé; Grieve, Kate (Frontiers in Medicine, 2022)
Time-lapse imaging facilitates the identification of structural continuity in changing environments. Hence, it may contribute to a better understanding of the structural evolution of the retina in the changing environment of retinal disease. Geographic atrophy (GA), the dry form of age-related macular degeneration, causes complex micrometric changes, the evolution of which is not yet well understood.In this retrospective study, we performed time-lapse imaging in 6 cases of GA using infrared scanning laser ophthalmoscopy (SLO) and optical coherence tomography (OCT) covering a mean period of 32.8 months (range, 18-72). The mean interval between imaging sessions was 2.4 months (range, 1.4-3.8).Viewing time-lapse sequences revealed a variety of changes that occurred in synchrony with atrophy progression. The most striking were those affecting pigmented spot along margins of atrophy, that is, on the non atrophic side of the retina; a continuum between the successive positions of hyperpigmented spots was detected, both by SLO and OCT. This continuum resulted in a subjective effect of centrifugal motion ahead of atrophy progression. Some apparent displacement of spots could be followed over several years and several hundred microns. A similar behavior was detected in pigmented spots located several hundred microns away from margins, suggesting that the pathological process causing atrophy expansion extends beyond the atrophy limits. These results highlight the interest of multimodal time-lapse imaging to detect cell-scale dynamics during progression of retinal diseases.